Kendali Radio Repeater Komunikasi Dua Meter Band Menggunakan Sistem Telekontrol Dual Tone Multi-Frequency - Aldi Rinaldi; Samuel Kristiyana; Wiwik Handajadi (Institut Teknologi Dirgantara Adisutjipto, 2021)
Repeater strongly supports the use of radio communication equipment for communication. The location of the repeater is usually at a high altitude so that the repeater's radio wave beam is not blocked by anything. The repeater arrangement is done by going directly to the repeater location so it is very inefficient from the time and accommodation factor. Therefore, a study was conducted to control the radio repeater settings remotely in order to reduce the accommodation of repeater control by visiting the radio repeater location. Control of radio repeater settings uses DTMF (Dual Tone Multi-Frequency) technology which sends DTMF signals and then converts them to binary data to be processed into data that is used for repeater control such as turning on and off the radio, setting high and low power, and adjusting channels on the repeater. the radio repeater. This system is also equipped with sending notifications in the form of SMS of the repeater operational conditions or settings. The research resulted in a remote control system based on DTMF technology equipped with a GSM/GPRS SIM800L module which is used to connect a smartphone to the system and send repeater operational notifications after controlling the repeater setting function. By using Telkomsel provider, the resulting delay when sending orders is 0.5 seconds and the delay in receiving SMS notifications is 12.96 seconds. Meanwhile, using Indosat provider, the resulting delay when sending commands is 0.43 seconds and the delay in receiving SMS notifications is 10.57 seconds.